A morphological analysis of Kemunasukuma personal names - Shigini, Peter Gonga; Mapunda, Gastor Cosmas (Linguistik Online, 2023)
Personal names and naming practices are among the linguistic topics that have occupied scholarly attention from diverse fields: philosophy, history, anthropology, linguistics, and psychology. This paper investigates personal names from a linguistic perspective. It examines Kemunasukuma personal names by focusing on their structural patterns and the morphological processes involved in their formation. The study followed a qualitative approach as it deals with textual data (personal names). Data was collected through interviews and documentary review, and morphological approaches were adopted in data analysis. Personal names were broken down into meaningful morphemes to trace their structural patterns as well as determine the word-formation processes involved. The findings indicate that Kemunasukuma personal names exhibit seven structural patterns that range from simple to complex. Also, the findings indicate that three word-formation processes: inflection, derivation, and compounding are productive and responsible for the formation of Kemunasukuma personal names. The structure of Kemunasukuma personal names not only points to the structure of the Sukuma language but also gives vital clues about their semantics.